Handbook of print media : technologies and production methods - Kipphan, Helmut; Kipphan, Helmut, 1943- (Berlin ; New York : Springer, 2001)
CD-ROM contains: Electronic version of text.
Includes bibliographical references and index.
System requirements for accompanying computer disc: Apple Macintosh or PC; Windows 95, 98, 2000, ME or Windows NT; Adobe Acrobat 5.0 (supplied); CD-ROM drive.
Keywords: Printing -- Handbooks, manuals, etc; Printing machinery and supplies -- Handbooks, manuals, etc; Printing industry -- Technological innovations -- Handbooks, manuals, etc